Modelling climate change impact on water resources of the Upper Indus Basin - Jamal H. Ougahi; Mark E. J. Cutler; Simon J. Cook (Journal of Water and Climate Change, 2022)
Climate change has implications for water resources by increasing temperature, shifting precipitation patterns and altering the timing of snowfall and glacier melt, leading to shifts in the seasonality of river flows. Here, the Soil & Water Assessment Tool was run using downscaled precipitation and temperature projections from five global climate models (GCMs) and their multi-model mean to estimate the potential impact of climate change on water balance components in sub-basins of the Upper Indus Basin (UIB) under two emission (RCP4.5 and RCP8.5) and future (2020–2050 and 2070–2100) scenarios. Warming of above 6 °C relative to baseline (1974–2004) is projected for the UIB by the end of the century (2070–2100), but the spread of annual precipitation projections among GCMs is large (+16 to −28%), and even larger for seasonal precipitation (+91 to −48%). Compared to the baseline, an increase in summer precipitation (RCP8.5: +36.7%) and a decrease in winter precipitation were projected (RCP8.5: −16.9%), with an increase in average annual water yield from the nival–glacial regime and river flow peaking 1 month earlier. We conclude that predicted warming during winter and spring could substantially affect the seasonal river flows, with important implications for water supplies. HIGHLIGHTS In the future, warming during winter could increase the proportion of rainfall compared to snowfall.; The streamflow from the Upper Indus River Basin is likely to increase in the future.; The early melting of snow during spring will greatly affect the timing of peak flows (earlier and less) from the sub-basins of the Upper Indus Basin.; The predicted changes in peak flows would have implications for hydroelectricity, industry and downstream irrigation.;